Tooth mortality in smokers and nonsmokers in a selected population in Sana'a, Yemen - Al-Bayaty, F.H.; Wahid, N.A.A.; Bulgiba, A.M. (2008)
Background and Objective: Tobacco smoking has been shown to be a major risk factor for tooth loss. The present study was designed to examine tooth mortality and the patterns of tooth loss in smokers and nonsmokers over a wide age range in a selected population from Sana'a, Yemen. Material and Methods: A total of 2506 persons between the ages of 15 and 64 years were examined, and every permanent tooth was assessed. Missing teeth included both extracted and missing teeth. Individuals currently smoking one or more boxes of cigarettes (20 cigarettes) a day for 5 years were considered as smokers, whereas individuals with no smoking history were considered as nonsmokers. Results: Smokers had a higher mean tooth loss than nonsmokers. The difference was statistically significant at p < 0.001. Mean tooth loss was significantly higher in smokers across all age groups, except for those in the 45-54 years age group. Smokers had a significantly higher mean upper tooth loss than nonsmokers. Tooth loss decreased from the incisors to the canines and then increased, with peak loss in the first molars. Conclusion: Tooth loss among smokers is significantly higher than among nonsmokers. The central incisors, lateral incisors and first molars were the most commonly missing teeth in smokers, compared with nonsmokers.